Ultra-thick steel material for flange with excellent strength and low-temperature impact toughness and manufacturing method thereof
Through the forging process of specific alloy composition and multiple forging ratio adjustment, combined with normalized heat treatment, the problem of central pores and surface defect control of ultra-thick steel when the thickness exceeds 200mm is solved, and the excellent strength and low-temperature impact toughness of the flange are achieved. , and maintains good surface quality.
Patent Information
- Application Number
- CN202380046635.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-05-22
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to ensure excellent strength, low-temperature impact toughness and good surface quality of the flange when manufacturing ultra-thick steel. Especially when the thickness exceeds 200mm, residual pores and surface defects in the center are difficult to effectively control, resulting in the structure being susceptible to layers. Damaged tear.
Using specific alloy composition and forging technology, including upsetting, forging circle and ring forging with multiple forging ratio adjustments in the range of 1100-1300℃, combined with normalized heat treatment, the carbon equivalent and hardenability index are controlled in the range of 0.35-0.55 Inside, the slab was manufactured at a cooling rate of 0.01-3°C/sec to ensure that the fine structure and porosity of the steel reached an optimized state.
Effectively compress the pores in the center of the steel, improve internal integrity, achieve tensile strength of 510-690MPa, yield strength of above 370MPa and low-temperature impact absorption energy of above 50J, ensuring excellent strength and low-temperature impact toughness of the flange. Maintain good surface quality.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a steel material that can be used for wind power towers and systems, and a method for manufacturing the same. More specifically, the present invention relates to an ultra-thick steel material for flanges having excellent strength and low-temperature impact toughness, and a method for manufacturing the same. Background Art
[0002] Wind turbines have attracted much attention as an environmentally friendly way of generating electricity, and include components such as tower flanges, bearings, and main shafts. Among them, the tower flange is a joint component required for connecting the tower, and 5 to 7 flanges are usually used in one tower. Since the tower flange is also installed at sea or in extremely cold areas, high durability is required. In particular, in order to meet the needs of large-capacity energy production and high efficiency, the scale of wind towers is also increasing, so the steel used is also constantly required to be high-strength, high-toughness, and high-thickness. As the thickness of the material increases, the total strain decreases, so the microstructure becomes larger, and the material shows a tendency to deteriorate due to defects in the material such as inclusions or segregation. Therefore, in order to improve the soundness of the inside and outside of the steel, the trend is to reduce the concentration or segregation of impurities such as non-metallic inclusions, or to control the cracks and pores on the surface and inside the material to the limit.
[0003] In particular, in the case of ultra-thick materials with a thickness exceeding 200mmt, the strain in the center of the material is not large. Therefore, when the unsolidified shrinkage holes generated during continuous casting or casting are not sufficiently compressed during the forging process, they remain in the center of the flange in the form of residual pores.
[0004] When the structure is subjected to axial stress through the thickness, these residual pores act as crack initiation points, resulting in damage to the entire device in the form of lamellar tearing. Therefore, before piercing (piercing forging) and ring forging (product forming) with less strain, the central pores need to be fully compressed so that there are no residual pores.
[0005] Patent document 1 related to this is a technology for applying a high reduction rate during the rough rolling of thick plates. Specifically, Patent document 1 uses a technology for determining the limit reduction rate of each thickness when plate bite occurs by setting a high reduction rate for each pass close to the design tolerance (load and torque) of the rolling mill, a technology for allocating the reduction rate by adjusting the index of the thickness ratio of each pass to ensure the target thickness of the rough rolling mill, and a technology for changing the reduction rate based on the limit reduction rate of each thickness to prevent the occurrence of plate bite, and provides a manufacturing method that can apply an average reduction rate of about 27.5% in the last three passes of rough rolling based on an 80mmt benchmark. However, the above rolling method measures the average reduction rate of the entire product thickness, and in the case of ultra-thick materials with a maximum thickness of more than 200mmt, there are technical difficulties in applying high strain to the central part where residual pores exist.
[0006] One of the other methods for manufacturing ultra-thick materials is a method using a forging machine having a higher effective variable per pass than that of a rolling mill. Patent document 2 discloses that a slab is subjected to hot forging with a cumulative reduction of 25% or more, the slab containing, in terms of mass%, C: 0.08-0.20%, Si: 0.40% or less, Mn: 0.5-5.0%, P: 0.010% or less, S: 0.0050% or less, Cr: 3.0% or less, Ni: 0.1-5.0%, Al: 0.010-0.080%, N: 0.0070% or less, and O: 0.0025% or less, satisfying the relationship of formula (1) and formula (2), and the remainder is given by F. e and unavoidable impurities, heated from a temperature above the Ac3 point to a temperature below 1200°C and hot rolled with a cumulative reduction of more than 40%, rapidly cooled from a temperature above the Ar3 point to a temperature below 350°C or below the Ar3 point, and manufactured by a tempering heat treatment process at a temperature of 450-700°C, wherein the material has a plate thickness of more than 100mmt, a yield strength of more than 620MPa, and an absorbed energy of more than 70J when evaluating the low-temperature impact toughness at -40°C.
[0007] However, in the manufacturing method, when the cumulative reduction is too high, surface defects may occur due to local strain concentration. In particular, when surface defects or sub-surface defects exist in the casting state before forging, the defects expand during the forging process, so the surface quality may be further deteriorated in the product state after rolling. In addition, when the forging reduction per pass is insufficient, even if the cumulative reduction is high, it is difficult to fully compress the pores remaining in the center, and since the effective variable in the center is smaller than the strain of the surface layer, the rolling process is not suitable for controlling the pores and structure of the center of the ultra-thick material.
[0008] In addition, Patent Document 3 discloses a process in which a material having a predetermined alloy composition can be heated to 1200-1350°C, hot forged with a cumulative reduction of more than 25%, heated to above the Ac3 point and below 1200°C, hot rolled with a cumulative reduction of more than 40%, then heated to above the Ac3 point and below 1050°C, rapidly cooled from a temperature above the Ac3 point to a lower temperature of below 350°C or below the Ar3 point, and tempered at a temperature in the range of 450-700°C, thereby manufacturing a high-strength steel plate with a yield strength of more than 620 MPa and a thickness of more than 100 mmt.
[0009] However, the above-mentioned ultra-high strength steel plate has a high carbon equivalent (Ceq) and hardenability index (DI), and therefore may be susceptible to surface cracks during casting, and in the case of steel for flanges manufactured by normalizing heat treatment, the relevant process conditions may not be easily applied. In addition, when the carbon equivalent (Ceq) and hardenability index (DI) are high, cracks are easily generated in the surface layer of the casting due to the hard structure of the surface layer generated during the secondary cooling process of steelmaking, and the cracks extend during the forging process, resulting in deterioration of the surface quality of the final product.
[0010] Therefore, a method of improving the internal integrity of a final product by forging by compressing the central pores has been proposed, but there is no practical method for simultaneously ensuring both suitable material quality and excellent surface quality of a steel material for a flange.
[0011] [Prior art literature]
[0012] [Patent Document]
[0013] (Patent Document 1) Korean Patent Publication No. 10-2012-0075246 (published on July 6, 2012)
[0014] (Patent Document 2) Korean Patent Publication No. 10-2017-0095307 (published on August 22, 2017)
[0015] (Patent Document 3) Korean Patent Publication No. 10-2017-0095307 (published on August 22, 2017) Summary of the invention
[0016] 1. Technical issues to be resolved
[0017] Therefore, an object of the present invention is to provide an ultra-thick steel material for flanges having excellent strength and low-temperature impact toughness and a method for manufacturing the same.
[0018] The technical problems to be solved by the present invention are not limited to the above contents. It is not difficult for those skilled in the art to understand the additional technical problems of the present invention from the overall content of this specification.
[0019] (II) Technical solution
[0020] One aspect of the present invention relates to an ultra-thick steel material for flanges, which comprises, by weight%, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: less than 0.01%, S: less than 0.015%, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, the balance Fe and other inevitable impurities, the Ceq of the ultra-thick steel material according to the following relationship 1 satisfies the range of 0.35 to 0.55, the ultra-thick steel material has a thickness of 200-500 mm, the ultra-thick steel material has a steel material fine structure composed of a composite structure of ferrite and pearlite with an average grain size of 30 μm or less, the maximum size of cementite existing in the ferrite-ferrite grain boundary and / or the ferrite-pearlite grain boundary is 5 μm or less, and the porosity of the product center is 0.1 mm 3 / g or less, the product center is the area 3 / 8t to 5 / 8t (where t is the thickness of the steel (mm)) from the surface of the steel in the thickness direction, and the fine NbC or NbCN precipitates with a diameter of 5-15nm are observed in the cross section of the steel for every 1μm 2 5 or more.
[0021] [Equation 1]
[0022] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15
[0023] In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and if these components are not intentionally added, 0 is substituted.
[0024] In addition, the tensile strength of the steel may be 510-690 MPa, the yield strength may be above 370 MPa, and the absorbed energy value of the Charpy impact test at -50°C may be above 50 J.
[0025] The maximum surface crack depth of the steel material may be less than or equal to 0.1 mm (including 0).
[0026] In addition, another aspect of the present invention relates to a method for manufacturing an ultra-thick steel material for a flange, the manufacturing comprising the following steps: manufacturing a slab, the slab comprising, in weight %, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, the balance Fe and other inevitable impurities, the Ceq of the slab according to the following relationship 1 satisfies the range of 0.35 to 0.55, and the slab has a thickness of 500 mm or more. thickness; heating the prepared slab to a temperature range of 1100-1300° C., and then performing a primary upsetting at a forging ratio of 1.3 to 2.4; after the primary upsetting, performing a bloom forging at a forging ratio of 1.5 to 2.0; reheating the material forged from the bloom to a temperature range of 1100-1300° C., and then performing a round forging at a forging ratio of 1.65 to 2.25, and then performing a secondary upsetting at a forging ratio of 1.3 to 2.3; The material subjected to the secondary upsetting is subjected to a tertiary upsetting at a forging ratio of 2.0 to 2.8, and then hole processing is performed; the material subjected to the hole processing is reheated to a temperature range of 1100-1300°C, and then ring forged at a forging ratio of 1.0 to 1.6; and normalizing heat treatment is performed, wherein the material subjected to the ring forging is heated to a temperature range of 820-930°C based on the temperature measurement of the center part of the material and maintained for 5-600 minutes, and then air-cooled to room temperature.
[0027] [Equation 1]
[0028] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15
[0029] In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and if these components are not intentionally added, 0 is substituted.
[0030] The slab may be manufactured by using one of a continuous casting process, a semi-continuous casting process and an ingot casting process.
[0031] After manufacturing the slab, the grain size of the prior austenite in the surface layer of the slab before forging is preferably 1000 μm or less, and the fine structure of the surface layer of the slab before forging is preferably composed of a composite structure of more than 15% polygonal ferrite and the remainder bainite.
[0032] When the initial size is 700 mm×1800 mm, the size of the forging surface punched during the first upsetting may be 1000-1200 mm×1800-2000 mm.
[0033] When the initial size is 1000-1200mm×1800-2000mm, the size of the forging surface of the bloom after forging is completed may be 1450-1850mm×2100-2500mm.
[0034] When the forging and secondary upsetting are completed, the size of the product can be 1450-1850Ø×1300-1700mm.
[0035] When the three upsetting steps are completed, the size of the product may be 2300-2800Ø×400-800mm.
[0036] The maximum thickness of the flange made of the steel material may be 200-500 mm, the inner diameter may be 4000-7000 mm, and the outer diameter may be 5000-8000 mm.
[0037] During the normalizing heat treatment, the heat treatment is preferably performed so that the LMP defined by the following relational expression 2 satisfies 20 to 33.
[0038] [Equation 2] LMP = T (Logt + 20) × (1 / 1000)
[0039] In the above relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
[0040] After the normalizing heat treatment, when the steel is welded, the steps of post-weld heat treatment, stress relieving heat treatment or tempering heat treatment may be further included.
[0041] The heat treatment after welding is preferably performed in a range where the value LMP defined by the following relational expression 2 is 19.3 or less.
[0042] [Equation 2] LMP = T (Logt + 20) × (1 / 1000)
[0043] In the relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
[0044] In addition, the present invention relates to a method for manufacturing an ultra-thick steel material for a flange, the manufacturing method comprising the following steps: when using molten steel to manufacture a slab, cooling the ingot discharged from the mold to a temperature range of 800-850°C at a cooling rate of 0.01-3°C / second to manufacture the slab, wherein the molten steel contains, by weight%, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0 .1%, P: less than 0.01%, S: less than 0.015%, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, the balance of Fe and other inevitable impurities, the molten steel is based on the following conditions The Ceq of formula 1 satisfies the range of 0.35 to 0.55; the prepared slab is heated to a temperature range of 1100-1300°C, and then subjected to a primary upsetting at a forging ratio of 1.3 to 2.4; after the primary upsetting, the raw billet is forged at a forging ratio of 1.5 to 2.0; the material forged by the raw billet is reheated to a temperature range of 1100-1300°C, and then subjected to rounding at a forging ratio of 1.65 to 2.25, and then subjected to a forging ratio of 1.3 to 2.3. The material subjected to the secondary upsetting is subjected to a tertiary upsetting at a forging ratio of 2.0 to 2.8, and then hole processing is performed; the material subjected to the hole processing is reheated to a temperature range of 1100-1300°C, and then ring forged at a forging ratio of 1.0 to 1.6; and a normalizing heat treatment is performed, wherein the material subjected to the ring forging is heated to a temperature range of 820-930°C based on the temperature measurement of the center portion of the material and maintained for 5-600 minutes, and then air-cooled to room temperature.
[0045] [Equation 1]
[0046] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15
[0047] In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and if these components are not intentionally added, 0 is substituted.
[0048] During the normalizing heat treatment, the heat treatment is preferably performed so that the LMP defined by the following relational expression 2 satisfies 20 to 33.
[0049] [Equation 2] LMP = T (Logt + 20) × (1 / 1000)
[0050] In the relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
[0051] (III) Beneficial effects
[0052] The present invention having the above-mentioned structure can effectively provide an ultra-thick steel material for flanges having excellent strength and low-temperature impact toughness by optimizing the forging process to compress the pores in the center of the steel material to improve the internal integrity of the final product. Best Mode for Carrying Out the Invention
[0053] The present invention relates to an ultra-thick steel material for flanges having excellent strength and low-temperature impact toughness and a method for manufacturing the product, and a preferred specific embodiment of the present invention will be described below. The specific embodiment of the present invention can be modified in various forms, and it should not be interpreted that the scope of the present invention is limited to the specific embodiment described below. This specific embodiment is provided to explain the present invention in more detail to those skilled in the art.
[0054] Hereinafter, the extra-thick steel material for flange of the present invention will be described in more detail.
[0055] The ultra-thick steel material for flanges of the present invention comprises, by weight%, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: less than 0.01%, S: less than 0.015%, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1. 0%, Ca: 0.0005-0.004%, the balance Fe and other inevitable impurities, the Ceq of the ultra-thick steel according to relational expression 1 satisfies the range of 0.35 to 0.55, the ultra-thick steel has a thickness of 200-500 mm, the ultra-thick steel has a steel microstructure consisting of a composite structure of ferrite and pearlite with an average grain size of less than 30 μm, the maximum size of cementite existing in ferrite-ferrite grain boundaries and / or ferrite-pearlite grain boundaries is less than 5 μm, and the porosity of the central part of the product is 0.1 mm 3 / g or less, the product center is a region 3 / 8t to 5 / 8t (where t refers to the thickness of the steel (mm)) from the surface of the steel in the thickness direction, and fine NbC or NbCN precipitates with a diameter of 5-15nm are observed in the cross section of the steel for every 1μm 2 5 or more.
[0056] The alloy composition of the present invention is described in more detail below. Unless otherwise specified, % and ppm described about the alloy composition are based on weight.
[0057] Carbon (C): 0.05-0.20%
[0058] Carbon (C) is the most important element to ensure basic strength, so it needs to be included in steel in an appropriate range. In order to achieve this addition effect, more than 0.05% carbon (C) can be added. Preferably, more than 0.10% carbon (C) can be added. On the other hand, when the content of carbon (C) exceeds a certain level, the fraction of pearlite increases during normalizing heat treatment, and may excessively exceed the strength and hardness of the parent material, so surface cracks are generated during forging, and the low-temperature impact toughness and anti-lamellar tearing properties in the final product may be reduced. Therefore, the content of carbon (C) in the present invention can be limited to 0.20%. The upper limit of the more preferred content of carbon (C) can be 0.18%.
[0059] Silicon (Si): 0.05-0.50%
[0060] Silicon (Si) is a replacement element, improves the strength of steel by solid solution strengthening, and has a strong deoxidation effect, and is therefore an essential element for manufacturing clean steel. Therefore, more than 0.05% silicon (Si) can be added, and more preferably, more than 0.20% silicon (Si) can be added. On the other hand, when a large amount of silicon (Si) is added, silicon (Si) may produce a martensite-austenite (Martensite-Austenite, MA) phase, and excessively increase the matrix strength, which may lead to the deterioration of the surface quality of ultra-thick material products, so the upper limit of the content of silicon (Si) can be limited to 0.50%. The upper limit of the content of more preferably silicon (Si) can be 0.40%.
[0061] Manganese (Mn): 1.0-2.0%
[0062] Manganese (Mn) is a useful element that improves strength and hardenability to produce low temperature transformation phases by solid solution strengthening. Therefore, in order to ensure a tensile strength of more than 550MPa, it is preferred to add more than 1.0% manganese (Mn). The content of more preferably manganese (Mn) can be more than 1.1%. On the other hand, manganese (Mn) can form non-metallic inclusions, i.e., MnS, that extend together with sulfur (S), thereby reducing toughness and acting as an impact starting point, so this may be a factor that significantly reduces the low temperature impact toughness of the product. Therefore, it is preferred that the content of manganese (Mn) is controlled to be less than 2.0%, and the content of more preferably manganese (Mn) can be less than 1.5%.
[0063] Aluminum (Al): 0.005-0.1%
[0064] Aluminum (Al) is one of the strong deoxidizers in the steelmaking process together with silicon (Si), and it is preferable to add 0.005% or more of aluminum (Al) to achieve this effect. A more preferred lower limit of the content of aluminum (Al) may be 0.01%. On the other hand, when the content of aluminum (Al) is excessive, Al in the oxide inclusions generated as a product of deoxidation is 2 O 3 The excessive increase in the fraction of aluminum (Al) makes the size of inclusions coarse and makes it difficult to remove inclusions during refining, which may be a factor that reduces low-temperature impact toughness. Therefore, it is preferred that the content of aluminum (Al) be controlled to be less than 0.1%. A more preferred content of aluminum (Al) may be less than 0.07%.
[0065] Phosphorus (P): 0.010% or less (including 0%), Sulfur (S): 0.0015% or less (including 0%)
[0066] Phosphorus (P) and sulfur (S) are elements that cause embrittlement at grain boundaries or cause embrittlement by forming coarse inclusions. Therefore, in order to improve the resistance to embrittlement crack growth, it is preferred to limit phosphorus (P) to 0.010% or less and sulfur (S) to 0.0015% or less.
[0067] Niobium (Nb): 0.001-0.07%
[0068] Niobium (Nb) is an element that improves the strength of the base material by precipitating in the form of NbC or NbCN. In addition, niobium (Nb) dissolved during high-temperature reheating precipitates very finely in the form of NbC during rolling to suppress the recrystallization of austenite, thereby having the effect of refining the structure. Therefore, it is preferred to add niobium (Nb) of 0.001% or more, and the more preferred content of niobium (Nb) may be 0.005% or more. On the other hand, when niobium (Nb) is added excessively, undissolved niobium (Nb) is generated in the form of TiNb (C, N), which is a factor that suppresses low-temperature impact toughness, so it is preferred to limit the upper limit of the content of niobium (Nb) to 0.07%. The more preferred content of niobium (Nb) may be 0.065% or less.
[0069] Vanadium (V): 0.001-0.3%
[0070] Since vanadium (V) is almost completely re-solidified during reheating, the strengthening effect by precipitation or solid solution during subsequent rolling is not significant, but in the case of ultra-thick forged materials, the air cooling rate is very slow, so very fine carbonitrides are precipitated during cooling or additional heat treatment, thereby having the effect of improving strength. In order to fully obtain this effect, it is necessary to add more than 0.001% vanadium (V). The lower limit of the more preferred content of vanadium (V) can be 0.01%. On the other hand, when the content of vanadium is excessive, the hardness of the surface layer of the slab may be excessively increased due to high hardenability, which not only becomes a factor causing surface cracks, etc. during flange processing, but also the manufacturing cost increases sharply, so it is not commercially advantageous. Therefore, the content of vanadium (V) can be limited to less than 0.3%. The more preferred content of vanadium (V) can be less than 0.25%.
[0071] Titanium (Ti): 0.001-0.03%
[0072] Titanium (Ti) is a component that precipitates as TiN during reheating and significantly improves low-temperature toughness by inhibiting the growth of original austenite grains at high temperatures. In order to achieve this effect, it is preferred to add more than 0.001% titanium (Ti). On the other hand, when titanium (Ti) is added in excess, low-temperature toughness may be reduced due to blockage of the continuous casting nozzle or crystallization of its central portion. In addition, titanium (Ti) combines with nitrogen (N) to form coarse TiN precipitates in the central portion of the thickness, which may reduce the elongation of the product, thereby reducing the uniform elongation during forging and causing surface cracks. Therefore, the content of titanium (Ti) may be less than 0.03%. The preferred content of titanium (Ti) may be less than 0.25%, and the more preferred content of titanium (Ti) may be less than 0.018%.
[0073] Chromium (Cr): 0.01-0.30%
[0074] Chromium (Cr) is a component that forms a low temperature phase transformation structure by improving hardenability to improve yield strength and tensile strength. In addition, chromium (Cr) is a component that prevents strength reduction by slowing down the spheroidization rate of cementite. In order to achieve the above-mentioned effects, 0.01% or more of chromium (Cr) may be added. On the other hand, when the content of chromium (Cr) is excessive, M 23 C 6 The size and fraction of Cr-Rich coarse carbides increase, which may reduce the impact toughness of the product, and reduce the solid solubility of niobium (Nb) and the fraction of fine precipitates such as NbC in the product, so there may be a problem of reducing the strength of the product. Therefore, the present invention can limit the upper limit of the chromium (Cr) content to 0.30%. The preferred upper limit of the chromium (Cr) content can be 0.25%.
[0075] ·Molybdenum (Mo): 0.01-0.12%
[0076] Molybdenum (Mo) is an element that increases grain boundary strength and has a significant solid solution strengthening effect, and is an element that effectively contributes to improving the strength and ductility of the product. In addition, molybdenum (Mo) has the effect of preventing the reduction of toughness due to grain boundary segregation of impurity elements such as phosphorus (P). For the above-mentioned effect, more than 0.01% of molybdenum (Mo) can be added. However, molybdenum (Mo) is an expensive element, and when molybdenum (Mo) is added in excess, the manufacturing cost may increase significantly, so the upper limit of the content of molybdenum (Mo) can be limited to 0.12%.
[0077] Copper (Cu): 0.01-0.60%
[0078] Copper (Cu) can not only greatly improve the strength of the matrix by solid solution strengthening in ferrite, but also has the effect of inhibiting corrosion in a wet hydrogen sulfide atmosphere, so it is a favorable element in the present invention. For the effect as described above, more than 0.01% copper (Cu) may be included. The more preferred content of copper (Cu) may be more than 0.03%. However, when the content of copper (Cu) is excessive, the possibility of causing star cracks on the surface of the steel plate increases, and since copper (Cu) is an expensive element, there may be a problem of significantly increased manufacturing costs. Therefore, the present invention may limit the upper limit of the content of copper (Cu) to 0.60%. The preferred upper limit of the content of copper (Cu) may be 0.5%.
[0079] ·Nickel (Ni): 0.05-1.00%
[0080] Nickel (Ni) is an element that effectively helps to improve impact toughness and hardenability to improve strength by increasing stacking defects at low temperatures to promote cross slip of dislocations. For the above-mentioned effects, more than 0.05% nickel (Ni) can be added. The preferred nickel (Ni) content can be more than 0.10%. On the other hand, when nickel (Ni) is added in excess, the manufacturing cost may be increased due to high cost, so the upper limit of the content of nickel (Ni) can be limited to 1.00%. The upper limit of the preferred content of nickel (Ni) can be 0.80%.
[0081] Calcium (Ca): 0.0005-0.0040%
[0082] When calcium (Ca) is added after deoxidation with aluminum (Al), calcium (Ca) combines with sulfur (S) forming MnS inclusions to suppress the generation of MnS, and simultaneously forms spherical CaS, thereby suppressing the occurrence of cracks caused by hydrogen-induced cracking. In order to sufficiently form sulfur (S) contained as an impurity into CaS, it is preferred to add 0.0005% or more of calcium (Ca). However, when the amount of calcium (Ca) added is excessive, the calcium (Ca) remaining after CaS is formed combines with oxygen (O) to produce coarse oxide inclusions, which may be a factor that reduces lamellar tearing properties due to stretching and breaking during rolling. Therefore, the upper limit of the content of calcium (Ca) can be limited to 0.0040%.
[0083] Relation 1
[0084] In the present invention, it is required that Ceq according to the following relational formula 1 satisfies the range of 0.35 to 0.55. When Ceq according to the following relational formula 1 is less than 0.35, the fraction of pearlite decreases, and thus the tensile strength value of 510-690 MPa required for the present invention cannot be ensured, and when Ceq according to the following relational formula 1 exceeds 0.55, the fraction of pearlite exceeds 30%, and thus it is not easy to ensure the low-temperature impact energy value at -50°C. Therefore, in the present invention, it is preferred to limit Ceq to the range of 0.35 to 0.55.
[0085] [Equation 1]
[0086] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15
[0087] In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and if these components are not intentionally added, 0 is substituted.
[0088] The ultra-thick steel for flanges with excellent strength and low-temperature impact toughness and its products of the present invention may contain a balance of Fe and other inevitable impurities in addition to the above components. However, in the usual manufacturing process, undesirable impurities are inevitably mixed from the raw materials or the surrounding environment, so these impurities cannot be completely excluded. These impurities are well known to those skilled in the art, so all of them are not specifically mentioned in this specification. In addition, the further addition of effective ingredients other than the above components is not completely excluded.
[0089] In addition, the ultra-thick steel of the present invention has a steel microstructure composed of a composite structure of ferrite and pearlite with an average grain size of less than 30 μm. When the average grain size of ferrite exceeds 30 μm, the length of the crack path (CrackPath) during impact fracture is shortened, the ductile brittle transition temperature (Ductile Brittle Transition Temperature, DBTT) increases, and the low-temperature impact toughness deteriorates. Therefore, the crystal grain size of ferrite is preferably less than 30 μm.
[0090] In addition, the maximum size of cementite present in the crystal grain boundary (the crystal boundary between ferrite-ferrite and / or ferrite-pearlite) of the fine structure is preferably 5 μm or less. When the maximum size of the cementite exceeds 5 μm, the coarse cementite may act as an impact starting point, so the impact toughness deteriorates, the grain boundary strength decreases, and thus intergranular fracture is likely to occur, thereby reducing the impact toughness. Therefore, the maximum size of cementite is preferably 5 μm or less.
[0091] More preferably, the fraction of cementite present in the grain boundaries is controlled to be 3 area % or less.
[0092] In addition, the porosity of the central part of the ultra-thick steel product of the present invention is 0.1 mm. 3 / g or less, the product center is the area 3 / 8t to 5 / 8t (where t refers to the thickness of the steel (mm)) from the surface of the steel in the thickness direction.
[0093] In addition, in the ultra-thick steel material of the present invention, it is preferred that fine NbC or NbCN precipitates with a diameter of 5 to 15 nm are present per 1 μm. 2 When the number of the fine precipitates is less than 5, the precipitation strengthening effect becomes weak, and there may be a problem in ensuring the physical properties required by the present invention.
[0094] Furthermore, the ultra-thick steel material of the present invention may have a thickness of 200-500 mm.
[0095] In addition, the ultra-thick steel of the present invention may have a tensile strength of 510-690 MPa, a yield strength of 370 MPa or more, and an absorbed energy value of 50 J or more in a Charpy impact test at -50°C.
[0096] In addition, the maximum surface crack depth of the steel material may be 0.1 mm or less (including 0).
[0097] Next, a method for producing an extra-thick steel material for flanges according to another aspect of the present invention will be described in detail.
[0098] The method for manufacturing ultra-thick steel of the present invention comprises the following steps: when using molten steel having the composition as described above to manufacture a slab, the cast billet discharged from the mold is subjected to secondary cooling at a cooling rate of 0.01-3°C / second to a temperature range of 800-850°C, thereby manufacturing the slab; heating the manufactured slab to a temperature range of 1100-1300°C, and then performing a primary upset forging at a forging ratio of 1.3 to 2.4; performing a rough rolling forging at a forging ratio of 1.5 to 2.0 after the primary upset forging; and reheating the material forged by the rough rolling billet to a temperature range of 1100-1300°C. The material subjected to the secondary upsetting is subjected to a tertiary upsetting at a forging ratio of 2.0 to 2.8, and then hole processing is performed; the hole processing material is reheated to a temperature range of 1100-1300° C., and then ring forged at a forging ratio of 1.0 to 1.6; and a normalizing heat treatment is performed, wherein the material subjected to the ring forging is heated to a temperature range of 820-930° C. based on the temperature measurement of the center portion of the material and maintained for 5-600 minutes, and then air-cooled to room temperature.
[0099] Slab preparation
[0100] First, in the present invention, a slab is manufactured.
[0101] Preferably, when molten steel having the above-mentioned composition is used to manufacture a slab, the ingot discharged from the mold may be secondarily cooled at a cooling rate of 0.01-3°C / sec to a temperature range of 800-850°C, thereby manufacturing a slab.
[0102] The inventors of the present invention have conducted in-depth research on methods for manufacturing ultra-thick steel having physical properties suitable for flanges and having excellent strength, impact toughness and surface quality. In particular, they have realized that in making slabs with a thickness of 500 mm or more, in order to ensure the strength, toughness and surface quality of the final flange product, it is necessary not only to control the carbon equivalent (Ceq) of the slab within a certain range, but also the prior austenite grain size and the fraction of fine structure in the surface layer of the slab are effective conditions, thereby obtaining the present invention.
[0103] The casting speed of a large-section casting machine for manufacturing a slab with a thickness of 650 mm or more is 0.06-0.1 m / min, so the casting operation is performed at a significantly slower speed than that of a conventional casting machine (casting speed: 0.4-1.5 m / min) for manufacturing a slab with a thickness of 250-400 mm. Therefore, when manufacturing a slab with a thickness of 500 mm or more, the retention time in the mold becomes relatively long, so austenite is in an environment where it can grow coarser.
[0104] As the size of the initial austenite grains increases, the manganese (Mn) segregation index of the austenite grain boundaries increases, and the grain boundary strength decreases, while the hardenability increases, so the fraction of hard bainite and martensite in the surface portion of the slab increases, rather than soft ferrite and pearlite. The uniform elongation of the hard structure is low, so when thermal deformation or external deformation or stress is applied, intergranular cracking may be easily generated. Therefore, when the grain size of the prior austenite (Prior Austenite) on the surface of the slab is large, intergranular cracking on the surface of the slab may be more actively generated, and the depth of the crack introduced in the subsequent high strain process such as forging and rolling may be further increased. Therefore, it is very important to control the grain size of the prior austenite below an appropriate level and ensure that the proportion of the grain boundary polygonal ferrite as a soft phase is above an appropriate level to suppress the surface cracking of the final product.
[0105] That is, in the present invention, the prior austenite grain size of the slab surface layer is preferably 1000 μm or less, and the microstructure thereof is preferably composed of a composite structure of 15 area % or more of polygonal ferrite and the remainder of bainite.
[0106] In order to reduce the prior austenite grain size and ensure that the fraction of polygonal ferrite is 15 area % or more, there is a scheme to design the components of carbon (C), nickel (Ni), chromium (Cr) and molybdenum (Mo) which have a solute dragging effect or a pinning effect to be higher. However, when the components of these carbon (C), nickel (Ni), chromium (Cr) and molybdenum (Mo) increase, the carbon equivalent (Ceq) also increases, and a low-temperature phase transformation structure may be generated during the cooling process of the slab. Therefore, the present invention can limit the carbon equivalent (Ceq) of the steel billet according to the following relationship 1 to less than 0.55. The preferred carbon equivalent (Ceq) may be 0.4 to 0.53.
[0107] [Equation 1]
[0108] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15
[0109] In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and if these components are not intentionally added, 0 is substituted.
[0110] In addition, when a slab is made from molten steel using a continuous casting process or a semi-continuous casting process, the surface temperature of the slab is water-cooled to a temperature of 800-850°C at a cooling rate of 0.01-3°C / second immediately after the casting speed is removed from the mold and then air-cooled. When the surface cooling rate is too slow, the austenite grains continue to grow, so the AGS of the surface cannot be finely controlled. When the surface cooling rate exceeds 3°C / second, surface cracks may occur during the cooling process due to the formation of the surface hard phase and the increase in the temperature gradient between the surface and the interior. When the target temperature is also lower than 800°C, a local low-temperature phase transformation structure may be formed. When the target temperature exceeds 850°C, it is difficult to control the AGS to less than 1000μm required by the present invention, so the appropriate surface quality cannot be ensured.
[0111] Heating and primary upsetting
[0112] Next, in the present invention, the prepared slab may be heated to a temperature range of 1100-1300° C. and then subjected to a primary upset forging at a forging ratio of 1.3 to 2.4.
[0113] The prepared slab may be heated to a temperature in the range of 1100-1300° C. As mentioned above, the thickness of the slab may be above 500 mm, and preferably above 700 mm.
[0114] The slab needs to be heated to a temperature range above a certain temperature range to allow the composite carbonitrides of titanium (Ti) or niobium (Nb), coarsely crystallized TiNb (C, N), etc. formed during the casting process to be re-solidified. In addition, before the first upsetting, the slab is heated and maintained above the recrystallization temperature to homogenize the structure, and is heated to a temperature range above a certain temperature range so that the forging termination temperature is high enough to minimize surface cracks that may occur during the forging process. Therefore, the heating of the slab of the present invention is preferably performed at a temperature range of 1100°C or above.
[0115] On the other hand, when the heating temperature of the slab is too high, high temperature scale may be excessively generated, and the manufacturing cost may be excessively increased due to high temperature heating and maintenance. Therefore, the heating of the slab of the present invention is preferably performed in the range of 1300°C or less.
[0116] In addition, upsetting is a method of rigid plastic deformation vertically with the length direction as the axis, and the forging ratio during a suitable upsetting can be 1.3 to 2.4, and more preferably 1.5 to 2.0. Among them, the forging ratio refers to the ratio of the cross-sectional area changed by forging. When the initial size is 700mm×1800mm, the size of the forged surface punched during a single upsetting can be 1000-1200mm×1800-2000mm.
[0117] When the forging ratio during the primary upsetting is less than 1.3, it is difficult to fully compress the porosity remaining in the center of the slab. Therefore, it is difficult to control the porosity required for the final product of the invention to 0.1 mm. 3 / g or less, so it is not easy to ensure the low-temperature impact toughness of the center of the slab. On the other hand, when the forging ratio during the single upset forging exceeds 2.4, bending occurs during the forging process, making it difficult to control the surface quality and proper shape required for the flange product. Therefore, the forging ratio during the single upset forging is preferably 1.3 to 2.4.
[0118] Bloom forging (forging of upper and lower surfaces)
[0119] Furthermore, in the present invention, the primary upset material is subjected to bloom forging at a forging ratio of 1.5 to 2.0.
[0120] Bitumen forging is a method of processing a material that has been upset once into a shape of a slab by further compressing the material that has been upset once, and is a method of expanding the area by processing the upper and lower surfaces in a certain direction of width or length. In the case of the slab forging, when the initial size is 1000-1200mm×1800-2000mm, the size of the forged surface when forging is completed can be 1450-1850mm×2100-2500mm. In the case of slab forging, a suitable forging ratio is 1.5 to 2.0. This is because when the forging ratio is less than 1.5, it is difficult to ensure the appropriate pore quality required by the present invention as in upset forging, and when the forging ratio exceeds 2.0, surface cracks may occur.
[0121] The forging direction is possible in both the length direction and the width direction, but in the length direction, the casting structure is configured to be more dense, so the elongation of the surface layer can be increased and the workability can be excellent. Therefore, considering the surface cracks, the length direction of the initial billet forging may be more suitable than the width direction.
[0122] Reheating and rounding - secondary upsetting
[0123] Furthermore, in the present invention, the material forged from the bloom is reheated to a temperature range of 1100-1300° C., then rounded at a forging ratio of 1.65 to 2.25, and then secondary upset at a forging ratio of 1.3 to 2.3.
[0124] When the bloom forging is finished, the bloom surface temperature is below 950°C, and when processing is continued, surface cracks or material fractures may occur. Therefore, after the bloom forging, the material can be heated again to a temperature range of 1100°C to 1300°C. As described above, heating at above 1100°C is preferred for reasons such as re-dissolving the crystallized material, homogenizing the structure, and preventing surface cracks, and the material is preferably controlled below 1300°C due to problems such as excessive oxide scale and grain coarsening.
[0125] In the case of the initial rolled billet at the end of heating, rounding is performed to process the flange boundary into a round shape, and then secondary upsetting is applied again. When the rounding and secondary upsetting are completed, the size of the product can be 1450-1850Ø×1300-1700mm. The forging ratios during rounding and secondary upsetting can be 1.65 to 2.25 and 1.3 to 2.3, respectively. When the forging ratios during rounding and secondary upsetting are lower than the level required by the present invention, it is difficult to control the porosity of the central part of the final product to 0.1mm 3 / g or less, so it is not easy to ensure the low-temperature impact toughness of the center part. When the forging ratio exceeds the benchmark, the flange product cannot be processed into the desired shape due to problems such as bending, surface cracks and poor shape.
[0126] In order to control the shape after the secondary upsetting is completed, re-rounding may also be applied, and then heating may be performed under the same conditions as the above-mentioned reheating temperature.
[0127] Three-stage upsetting and hole processing
[0128] Furthermore, in the present invention, hole processing is performed after the material subjected to the second upset is subjected to the third upset at a forging ratio of 2.0 to 2.8.
[0129] The material processed into the cylindrical shape can be processed into the appropriate flange thickness by three-stage upsetting before hole processing (perforation). When the three-stage upsetting is completed, the size of the product can be 2300-2800Ø×400-800mm. The forging ratio of the three-stage upsetting can be 2.0 to 2.8. When the forging ratio is insufficient or exceeded, the problem of being unable to control the above-mentioned residual porosity and surface cracks / shape may occur. After the three-stage upsetting is completed, a punch of 500-1000Ø can be used to punch a hole in the center of the material.
[0130] Reheating and ring forging
[0131] Subsequently, in the present invention, the hole-processed material is reheated to a temperature range of 1100-1300° C. and then ring forged at a forging ratio of 1.0 to 1.6.
[0132] The material processed by the hole is reheated to a temperature within the range of 1100-1300°C, and then can be processed into the final flange ring shape. The maximum thickness of the flange made of the steel can be 200-500mm, the inner diameter can be 4000-7000mm, and the outer diameter can be 5000-8000mm. Ring forging does not apply rigid plastic processing because controlling the final shape and size is an important process rather than compressing the pores. Therefore, the forging ratio can be 1.0 to 1.6, and more preferably 1.2 to 1.4.
[0133] In addition, the strain rate in all the forging processes proposed above in the present invention may be 1 / second to 4 / second. At a strain rate of less than 1 / second, the temperature of the fine forging may be reduced, and surface cracks may occur. On the other hand, when a high strain rate exceeding 4 / second is applied in the non-recrystallized zone, surface cracks may occur due to a decrease in elongation caused by excessive local work hardening.
[0134] Normalizing heat treatment
[0135] Finally, in the present invention, a normalizing heat treatment may be performed, wherein the flange product after forging is heated to a temperature range of 820-930° C. based on the temperature measurement of the product center portion and maintained for 5-600 minutes, and then air-cooled to room temperature.
[0136] During the normalizing heat treatment, when the heating temperature is lower than 820°C or the holding time is less than 5 minutes, the carbides generated during the cooling process after forging or the impurity elements segregated at the grain boundaries cannot be smoothly re-solidified, so the low-temperature toughness of the steel after heat treatment may be greatly reduced. On the other hand, during the normalizing heat treatment, when the heating temperature exceeds 930°C or the holding time exceeds 600 minutes, the grain size of the ferrite matrix phase of the ferrite pearlite composite structure exceeds the 30μm required by the present invention or the strength and low-temperature impact toughness may deteriorate due to the coarsening of precipitated phases such as Nb(C,N) and V(C,N).
[0137] In addition, in the present invention, it is preferred that the flange material subjected to the ring forging be subjected to normalizing heat treatment under the condition that LMP defined by the following relational expression 2 satisfies 20 to 33.
[0138] The normalizing heat treatment and holding time can be expressed by the following Larson-Miller Parameter Formula 2 (Reference: FR Larson and J. Miller: Trans. ASME, 1952, vol. 74, pp. 765-75). In order to meet the impact toughness required by the present invention by refining the size of the pearlite domain (Coloney), the LMP of the normalizing temperature and time conditions can be 20 to 23.
[0139] [Equation 2] LMP = T (Logt + 20) × (1 / 1000)
[0140] In the relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
[0141] When the LMP is less than 20, there is a disadvantage that material deviation may occur due to insufficient heating to the austenite single phase region or uneven diffusion of the solute. When the LMP exceeds 23, excessively coarse ferrite and pearlite domains are generated, making it difficult to ensure the low-temperature impact toughness required by the present invention.
[0142] In addition, in the present invention, after the normalizing heat treatment, when welding is performed, a post-welding heat treatment, a stress relief heat treatment, or a tempering heat treatment may be performed. This post-welding heat treatment may be performed within the range of a value LMP defined by the relational expression 2 of 19.3 or less. When the LMP exceeds 19.3, the size of the grain boundary cementite increases, exceeding the 5 μm required for the invention, and thus the impact toughness may deteriorate. Therefore, when welding, the LMP of the subsequent heat treatment is preferably 19.3 or less. DETAILED DESCRIPTION
[0143] The present invention is described in detail below by way of examples. However, it should be noted that the following examples are only used to illustrate the present invention in more detail and are not intended to limit the scope of the present invention.
[0144] (Example)
[0145] [Table 1]
[0146]
[0147] * In Table 1, the content of the component elements is expressed in wt %, but the content of P, S, and Ca is expressed in ppm. The remaining components are Fe and unavoidable impurities.
[0148] A slab having a thickness of 700 mm and having the alloy composition of Table 1 was manufactured. Using this slab, a slab was prepared by cooling according to the process conditions of Table 2 below, and then a flange having a final thickness of 320 mmt was manufactured by forging process (reheating and primary upsetting, bloom forging, reheating-secondary upsetting, tertiary upsetting, reheating and ring forging) and normalizing heat treatment. The process conditions satisfying the scope of the present invention were applied to the processes other than the processes described in Table 2.
[0149] After that, the physical property values of the prepared test pieces were measured and shown in the following Table 3. Among them, the crystal grain size of the prior austenite and the fraction of polygonal ferrite (PF) in the surface layer of the slab were measured by collecting test pieces from the surface layer structure after casting and using an automatic image analyzer.
[0150] In addition, the ferrite grain size of the steel material was measured by taking a test piece from the final steel material structure and using an automatic image analyzer. In addition, the product microstructure of the invention example and the comparative example in this embodiment is a mixed structure of ferrite and pearlite.
[0151] In addition, the yield / tensile strength was evaluated by a room temperature tensile test, and in the case of the yield strength, a 0.2% offset was applied. In addition, the impact toughness of each test piece was measured by the Charpy V-Notch Test at the corresponding temperature using the average of the absorbed energy values measured three times.
[0152] In addition, the number of NbC precipitates in the cross section of the steel material was measured using TEM. The NbC precipitates were confirmed by the diffraction pattern of NbC and EDX mapping, and the number of NbC precipitates located at 1 μm was counted. 2 The number of NbC precipitates.
[0153] By measuring the density (g / mm 3 ) and take the reciprocal (mm 3 / g) to measure the porosity of the central part of the product.
[0154] In addition, after visually observing the surface of each test piece, grinding was performed at the position where the surface crack was formed, and the grinding length until the crack disappeared was measured as the surface crack length. In the case of a through crack, the crack is not limited to the surface layer part, and corresponds to the case of penetrating into the inside, and the total length of the crack entry is measured by cutting the cross-section part.
[0155] [Table 2]
[0156]
[0157] [Table 3]
[0158]
[0159] * The number of precipitates in Table 3 refers to the number of fine NbC or NbCN precipitates with a diameter of 5-15 nm per 1 μm of precipitates observed in the cross section of the steel material. 2 The porosity refers to the porosity of the product center, which is the area 3 / 8t to 5 / 8t (where t refers to the thickness of the steel (mm)) from the surface of the steel in the thickness direction.
[0160] It can be seen from Tables 1 to 3 that in all cases of Invention Examples 1 to 7 that meet the alloy composition and manufacturing conditions proposed in the present invention, they have excellent strength and low-temperature impact toughness at -50°C, and ensure good surface quality in the flange product state.
[0161] On the other hand, Comparative Examples 1 to 15, Comparative Examples 21 to 22 are cases where the alloy composition proposed in the present invention is satisfied but the manufacturing conditions are not satisfied, and it can be seen that the strength and low-temperature impact toughness values are low because the grain size of the original austenite of the slab, the fraction of polygonal ferrite or the porosity of the central part, and the grain size of ferrite in the flange product state proposed in the present invention are not satisfied. In addition, even if the material is good, when the forging ratio conditions are not satisfied in each forging step, poor surface quality characteristics caused by the occurrence of surface cracks or through cracks can be determined in the product state.
[0162] In addition, Comparative Examples 16 to 20 meet the manufacturing conditions proposed by the present invention, but do not meet the alloy composition, so it can be seen that the quality level is low, such as excessive strength (insufficient impact toughness) or insufficient strength.
[0163] As mentioned above, the preferred embodiments of the present invention are described in the detailed description of the present invention, but those skilled in the art can make various modifications without departing from the scope of the present invention. Therefore, the scope of the present invention is not limited to the described embodiments, but should be determined by the claims and their equivalents.
Claims
1. An extra-thick steel material for flanges, wherein: The ultra-thick steel comprises, in weight%, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, the balance of Fe and other inevitable impurities, and the Ceq of the ultra-thick steel according to the following relationship 1 satisfies the range of 0.35 to 0.55, The super thick steel material has a thickness of 200-500 mm. The ultra-thick steel material has a steel material microstructure consisting of a composite structure of ferrite and pearlite with an average grain size of 30 μm or less. The maximum size of cementite present at the ferrite-ferrite grain boundary and / or the ferrite-pearlite grain boundary is 5 μm or less, The porosity of the product center is 0.1mm 3 / g or less, the center of the product is the area 3 / 8t to 5 / 8t away from the surface of the steel in the thickness direction, where t refers to the thickness of the steel in mm. In the precipitates observed in the cross section of the steel material, fine NbC or NbCN precipitates with a diameter of 5-15 nm are present per 1 μm. 2 5 or more, [Equation 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and the unit is weight %, and if these components are not intentionally added, 0 is substituted.
2. The ultra-thick steel material for flange according to claim 1, wherein: The steel has a tensile strength of 510-690 MPa, a yield strength of more than 370 MPa, and an absorbed energy value of more than 50 J in a Charpy impact test at -50°C.
3. The extra-thick steel material for flange according to claim 1, wherein: The maximum surface crack depth of the steel material is less than or equal to 0.1 mm.
4. The extra-thick steel material for flange according to claim 1, wherein: The fraction of cementite present in the ferrite-ferrite grain boundary or the ferrite-pearlite grain boundary is 3 area % or less.
5. A method for manufacturing an ultra-thick steel material for a flange, comprising the following steps: manufacturing a slab, wherein the slab comprises, in weight %, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, the balance Fe and other inevitable impurities, wherein Ceq of the slab according to the following relational formula 1 satisfies the range of 0.35 to 0.55, and the slab has a thickness of 500 mm or more; The prepared slab is heated to a temperature range of 1100-1300° C., and then subjected to a primary upsetting at a forging ratio of 1.3 to 2.4; After the primary upsetting, the bloom is forged at a forging ratio of 1.5 to 2.0; The material forged from the bloom is reheated to a temperature range of 1100-1300° C., then rounded at a forging ratio of 1.65 to 2.25, and then secondary upset at a forging ratio of 1.3 to 2.3; The material subjected to the secondary upsetting is subjected to a third upsetting at a forging ratio of 2.0 to 2.8, and then subjected to hole processing; The material processed through the hole is reheated to a temperature range of 1100-1300° C. and then ring forged at a forging ratio of 1.0 to 1.6; as well as Normalizing heat treatment, heating the ring forged material to a temperature range of 820-930°C based on the temperature of the center of the material and maintaining it for 5-600 minutes, and then air cooling it to room temperature, [Equation 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and the unit is weight %, and if these components are not intentionally added, 0 is substituted.
6. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: The slab is manufactured using a continuous casting process or a semi-continuous casting process.
7. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: After manufacturing the slab, the grain size of the prior austenite in the surface layer of the slab before forging is less than 1000 μm, and the microstructure of the surface layer of the slab before forging is composed of a composite structure of more than 15% polygonal ferrite and the remainder bainite.
8. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: When the initial size is 700 mm×1800 mm, the size of the forging surface punched during the first upsetting is 1000-1200 mm×1800-2000 mm.
9. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: When the initial size is 1000-1200mm×1800-2000mm, the size of the forging surface of the bloom after forging is completed is 1450-1850mm×2100-2500mm.
10. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: When the forging and secondary upsetting are completed, the size of the product is 1450-1850Ø×1300-1700mm.
11. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: When the three upsetting steps are completed, the size of the product is 2300-2800Ø×400-800mm.
12. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: The flange made of the steel material has a maximum thickness of 200-500 mm, an inner diameter of 4000-7000 mm, and an outer diameter of 5000-8000 mm.
13. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: During the normalizing heat treatment, the heat treatment is performed so that the LMP defined by the following relation 2 satisfies 20 to 33, [Equation 2] LMP=T(Logt+20)×(1 / 1000) In the relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
14. The method for manufacturing an ultra-thick steel material for flange according to claim 5, wherein: After the normalizing heat treatment, when the steel is welded, the process further includes a step of performing a post-welding heat treatment, a stress relief heat treatment or a tempering heat treatment.
15. The method for manufacturing an ultra-thick steel material for flange according to claim 14, wherein: The heat treatment after welding is performed in a range where the value LMP defined by the following relational expression 2 is less than 19.3, [Equation 2] LMP=T(Logt+20)×(1 / 1000) In the relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
16. A method for manufacturing an ultra-thick steel material for a flange, comprising the following steps: When the slab is manufactured using molten steel, the ingot discharged from the mold is subjected to secondary cooling at a cooling rate of 0.01-3°C / second to a temperature range of 800-850°C, thereby manufacturing the slab. The molten steel contains, by weight%, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: less than 0.01%, S: less than 0.015%, Nb:
0. 001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, the balance of Fe and other inevitable impurities, the Ceq of the molten steel according to the following relationship 1 satisfies the range of 0.35 to 0.55; The prepared slab is heated to a temperature range of 1100-1300° C., and then subjected to a primary upsetting at a forging ratio of 1.3 to 2.4; After the primary upsetting, the bloom is forged at a forging ratio of 1.5 to 2.0; The material forged from the bloom is reheated to a temperature range of 1100-1300° C., then rounded at a forging ratio of 1.65 to 2.25, and then secondary upset at a forging ratio of 1.3 to 2.3; The material subjected to the secondary upsetting is subjected to a third upsetting at a forging ratio of 2.0 to 2.8, and then subjected to hole processing; The material processed through the hole is reheated to a temperature range of 1100-1300° C. and then ring forged at a forging ratio of 1.0 to 1.6; as well as Normalizing heat treatment, heating the ring forged material to a temperature range of 820-930°C based on the temperature of the center of the material and maintaining it for 5-600 minutes, and then air cooling it to room temperature, [Equation 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above-mentioned relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] refer to the contents of C, Mn, Cr, Mo, V, Ni and Cu contained in each steel material, and the unit is weight %, and if these components are not intentionally added, 0 is substituted.
17. The method for manufacturing an ultra-thick steel material for flange according to claim 16, wherein: During the normalizing heat treatment, the heat treatment is performed so that the LMP defined by the following relational expression 2 satisfies 20 to 33, and the ultra-thick steel has excellent strength and low-temperature impact toughness. [Equation 2] LMP=T(Logt+20)×(1 / 1000) In the relational expression 2, T is the Kelvin reference temperature, t is the time, and the exponent of log is 10.
Citation Information
Patent Citations
Method and apparatus for roughing mill of thick steel sheet
KR1020120075246A
Thick high-toughness high-strength steel sheet and method for manufacturing same
KR1020170095307A